MENGOPTIMALKAN UPAYA PENCEGAHAN SENGKETA PERTANAHAN DEMI TERUTARAKANNYA SUMATERA UTARA - Zulfikar, Zulfikar; Syamantha, Talita (Lex Lectio Law Journal, 2023)
AbstractLand is one of the most important natural resources for human existence, more than just a place to live. This relationship includes the resources necessary for human survival. The prosperity of the people over land will be realized with the guarantee of proof of control of land rights. The issuance of proof of land rights is carried out to avoid land rights disputes that will occur in the community. In its regulation, the central government and local governments have the authority to provide legal certainty in the form of written evidence of control of a plot of land by the community. At the central government level, the authority is exercised by the National Land Agency, while at the local level it is delegated to the local government (Pemda) based on the principle of decentralization. So that in this study raises the formulation of the problem: (1) What are the factors that cause land disputes and how efforts can be made to optimize the prevention of land disputes This research is part of legal research. The method used is the normative juridical method, by examining the norms of legislation in the field of land disputes. Handling disputes in the land sector is a shared responsibility and authority between the National Land Agency (BPN) together with the Regional Government in accordance with statutory regulations. The position of the State Land Agency (BPN) as the only body or organization authorized to carry out the task of managing the land sector. BPN and local governments should work together in increasing their efforts to minimize land disputes. land dispute prevention efforts are an action taken to avoid land disputes between individuals or people with legal entities. Prevention efforts that can be done by the local government are the issuance of proof of rights for all people of North Sumatra, and launching pilot villages. Prevention efforts by the BPN are carried out by increasing the target of community land registration so that all land parcels are certified. AbstrakTanah merupakan salah satu sumber daya alam yang sangat penting bagi keberadaan manusia, lebih dari sekadar sebagai tempat tinggal. Hubungan ini mencakup sumber daya yang diperlukan untuk kelangsungan hidup manusia. Kemakmuran rakyat atas tanah akan terwujud dengan terjaminnya tanda bukti penguasaan hak atas tanah. Penerbitan tanda bukti hak atas tanah dilakukan untuk menghindari sengketa hak atas tanah yang akan terjadi di masyarakat.Didalam pengaturannya, pemerintah pusat dan pemerintah daerah memiliki kewenangan untuk memberikan kepastian hukum berupa bukti tertulis atas penguasaan sebidang tanah oleh masyarakat. Ditataran pemerintah pusat kewenangan tersebut dilaksanakan oleh Badan Pertanahan Nasional, sedangkan di tingkat daerah di delegasikan kepada pemerintah daerah (Pemda) berdasarkan azas desentralisasi. Sehingga dalam penelitian ini menimbulkan rumusan masalah: (1) Apa Sajakah Faktor yang Menyebabkan Sengketa Pertanahan dan Bagaimana Upaya yang Dapat Dilakukan untuk Mengoptimalkan Pencegahan Sengketa Pertanahan Penelitian ini merupakan bagian dari penelitian hukum. Metode yang digunakan adalah metode yuridis normatif, dengan meneliti norma-norma peraturan perundang-undangan dibidang sengketa pertanahan. Penanganan sengketa di bidang pertanahan merupakan tanggung jawab dan kewenangan bersama antara Badan Pertanahan Nasional (BPN) bersama-sama dengan Pemda sesuai dengan peraturan perundang-undangan. Kedudukan Badan Pertanahan Negara (BPN) sebagai satu-satunya badan atau organisasi yang diberi wewenang untuk melaksanakan tugas pengurusan bidang pertanahan.Sudah seharusnya BPN dan Pemda bersinergi dalam meningkatkan upayanya untuk meminimalisir sengketa pertanahan.upaya pencegahan sengketa pertanahan adalah suatu tindakan yang dilakukan untuk menghindari perselisihan pertanahan antara perorangan maupun orang dengan badan hukum. Upaya pencegahan yang dapat dilakukan oleh pemda adalah, penerbitan tanda bukti hak bagi seluruh masyrakat Sumatera Utara, dan mencanangkan desa percontohan. Upaya pencegahan oleh BPN dilakukan dengan meningkatkan target pendaftaran tanah masyarakat sehingga seluruh bidang tanah tersertifikatkan.